2018
DOI: 10.1111/mec.14891
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution of gene classes, but not genes: Evidence from Hawai'ian honeycreeper populations exposed to avian malaria

Abstract: Adaptation in nature is ubiquitous, yet characterizing its genomic basis is difficult because population demographics cause correlations with nonadaptive loci. Introduction events provide opportunities to observe adaptation over known spatial and temporal scales, facilitating the identification of genes involved in adaptation. The pathogen causing avian malaria, Plasmodium relictum, was introduced to Hawai'i in the 1930s and elicited extinctions and precipitous population declines in native honeycreepers. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 131 publications
0
26
0
Order By: Relevance
“…In the case of the amphibian study, RNAseq data after experimental infection revealed the role of MHC super-types in eliciting a massive immune response in dying versus surviving leopard frogs, and directional selection in response to fungal infection was implicated in the reduction of MHC diversity in a related species (see Savage et al 2016Savage et al , 2017. For honeycreepers, genomic analyses identified candidate loci that may facilitate survival after malarial infection in the amakihi (see Cassin-Sackett et al 2018). In the special issue we include one example based on the genomic context of susceptibility of the Tasmanian devil to facial tumours (Hohenlohe et al this issue).…”
Section: The Meeting and Discussionmentioning
confidence: 99%
“…In the case of the amphibian study, RNAseq data after experimental infection revealed the role of MHC super-types in eliciting a massive immune response in dying versus surviving leopard frogs, and directional selection in response to fungal infection was implicated in the reduction of MHC diversity in a related species (see Savage et al 2016Savage et al , 2017. For honeycreepers, genomic analyses identified candidate loci that may facilitate survival after malarial infection in the amakihi (see Cassin-Sackett et al 2018). In the special issue we include one example based on the genomic context of susceptibility of the Tasmanian devil to facial tumours (Hohenlohe et al this issue).…”
Section: The Meeting and Discussionmentioning
confidence: 99%
“…If knowledge of causal alleles is available, then one must demonstrate that a given site has been under repeated and independent selection in each replicate pair (Lee & Coop, 2017, 2019. Typically, these analyses are undertaken comparing individual replicate pairs (e.g., Roda et al, 2013b;Lamichhaney et al, 2017;Cassin-Sackett et al, 2019), although some studies detect broad, or 'global' outliers by comparing the aggregate of all populations within each ecotype (e.g., Jones et al, 2012;Kautt et al, 2012). In the absence of repeated selection on the same allele or gene, parallelism can be manifested at the functional level, such that different genes under selection participating in the same predicted biological function contribute to the pattern of phenotypic parallelism in a system.…”
Section: Genotypic Parallel Evolutionmentioning
confidence: 99%
“…In the absence of repeated selection on the same allele or gene, parallelism can be manifested at the functional level, such that different genes under selection participating in the same predicted biological function contribute to the pattern of phenotypic parallelism in a system. It is frequently asked whether predicted biological functions are consistently enriched across independent populations (Smith & Rausher, 2011;Kowalko et al, 2013;Roda et al, 2013b;Perreault-Payette et al, 2017;Cassin-Sackett et al, 2019). These analyses can inform us about how genotypically parallel a system is at different scales of divergence, so we can also view genotypic parallel evolution as broad-sense or narrow-sense ( Figure 1).…”
Section: Genotypic Parallel Evolutionmentioning
confidence: 99%
See 2 more Smart Citations